SCIENTIFIC WRITING TRAINING FOR CLASS XI STUDENTS OF SMA NEGERI 7 PADANG - Upit Yulianti; Rahayu Fitri; Trisna Helda (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2021)
The training activity of scientific writing for students of SMA Negeri 7 Padang has been carried out. The low interest and skills of students in writing a good and interesting scientific work is caused by the lack of students' knowledge of title writing, problem formulation, discussion writing, closing and bibliography writing, systematic writing of scientific papers, and linguistic rules in scientific works. The solution offered to these problems is to provide assistance in the form of providing motivation to increase interest in writing scientific papers. Scientific works can be written as the result of research or literature review. The training method is an activity filled with lectures, presentations, discussions, and mentoring of participants. Participants responded positively to the activity by showing enthusiasm during the activity and increasing participants' understanding of scientific writing. This activity can increase students' interest and skills in writing scientific papers.